Kikuchi–Fujimoto disease presenting as pyrexia of unknown origin - Prasanta Padhan; Krishna Prasad Tripathy; Saroj Ranjan Sahoo; Debasish Maikup; Nachiketa Mahapatra (Indian Journal of Rheumatology)
Kikuchi–Fujimoto disease (KFD), or histiocytic necrotizing lymphadenitis, is a rare benign, self-limiting disorder of unknown etiology. Mostly prevalent among Asian women, KFD manifests mostly with cervical and rarely generalized or retroperitoneal lymphadenopathy in addition to fever. It can closely mimic infective and immunological disorders. Here, we report a 23-year-old female who presented with fever of unknown origin with other constitutional symptoms. The infectious and malignancy screen was negative on extensive workup. The patient was found to have multiple abdominal and cervical lymph nodes on imaging, biopsy and immunohistochemistry revealed histiocytic necrotizing lymphadenitis, which confirmed the diagnosis of KFD. Although rare, clinicians should be aware of KFD condition, as early recognition of the disease will minimize potentially harmful and unnecessary evaluation and treatments.